Strategy to Increase Sugar Production at PT. Perkebunan Nusantara (PTPN) XIV Takalar Sugar Factory - A. Irga Satrawati Taslim (International Journal of Science, Technology & Management, 2021)
This study aims to formulate priority strategies to increase the production of sugar is right for PTPN XIV PG. Takalar. This research uses qualitative and quantitative approaches. The research was conducted by distributing questionnaires and in-depth interviews to informants. Then the data were analyzed by using Analysis Hierarchy Process. The results of this study indicate factors that affect the strategy of enhacement production of sugar in PTPN XIV PG. Takalar is the potential for a broad area of planting sugar cane, machine factories were already old, the increase in demand for sugar, and the disputed land. The priority order of the strategy is the first to utilize the land potential and factory capacity as well as the development of plant cultivation technology to improve the quality and yield of sugar with a weight of AHP value (0.150). On Priority two is optimalisasi utilization of land and the capacity of the plant by weighting the value of AHP (0.112). On Priority three is maximizing spacious land with the utilization of the development of technology of cultivation of plants with value weights AHP (0.098). On Priority, fourth is coordination between the authorities and the factory with value weights AHP (0.095). On Priority Fifth is utilization infrastructure marketing with value weights AHP (0.089). At priority, sixth is to strive to repair or renewal the machine factory with value weights AHP (0.051).